(untitled) (Damascus University Journal for legal sciences, 2023)
Comparative Arab legislation related to nationality differs in its position on the system of withdrawing citizenship and the extent to which the administration is allowed to exercise this authority. state and safety. If we examine the reasons for withdrawing citizenship in Arab legislation, we find that they are very similar. In this research, we will review the cases of withdrawal of citizenship in the legislation of a number of Arab countries (Syria, Egypt, Tunisia, Morocco) and indicate the points of similarity and difference between them.